Comparative Discourse of Smart City and Smart Village in Asia, Case of Indonesia, Malaysia, and Japan - Nugroho, Rino Ardhian; Berlian, Berlian; Wallang, Muslimin; Jamaluddin, Anif; Prakoso, Septyanto Galan; Andari, Rosita Novi (Universitas Padjadjaran, 2026)
Urban and rural areas worldwide face growing challenges from rapid population growth, climate change, and resource constraints. Governments are responding by adopting smart city and smart village initiatives that use technology to promote sustainable development. Yet, academic research on these topics differs markedly across countries due to distinct policy priorities, development needs, and research contexts. This study performs a comparative bibliometric analysis of smart city and smart village publications in Indonesia, Malaysia, and Japan, using Scopus-indexed data processed with VOSviewer. Results show Indonesia has effectively integrated both domains, with research evolving from a technology focus toward collaborative governance and sustainability. Japan, meanwhile, emphasizes systematic, infrastructure-driven smart city development, but its smart village studies remain disconnected from key rural issues like depopulation and aging populations. In Malaysia, smart village research predominantly centers on biomedical and public health themes rather than technology-based rural advancement, revealing a clear research gap. These findings can inform policymakers on research prioritization, guide funding toward underrepresented areas, and aid in creating balanced measurement frameworks that align global standards with local realities. Ultimately, although smart development concepts are global, their academic exploration and practical application must be adapted to each country’s unique context.